Research analytics on the applications of flexible formwork gob-side entry retention technology in medium-thickness coal seams with large inclination angles. - Xiaofan Cao; Song Wang; Xiaoli Wang; Zhongyu Yang; Ang Li (PLoS ONE)
Gob-side entry retention (GER) has been successfully advanced and implemented for several years. Notably, strong economic returns have been realised for different thicknesses of coal seams under near-horizontal and gently inclined conditions. However, implementing gob-side entry retention under the conditions of high dip angle or steeply inclined coal seam has always been difficult. This paper systematically introduces the material and construction processes of flexible formwork GER. Engineering practice, theoretical calculations and indoor test analysis were used to propose an independently designed and developed special-shaped flexible formwork concrete wall with a width of 1.2 m, a strength of C30 and an inclination angle of 20°. This wall was then used to investigate the GER technology in the No. 31342 working face of the Dachiba Coal Mine. The findings reveal that the strength of the developed coal solid waste flexible formwork concrete fulfils the design requirements, and the residual strength and healing capacity are superior to that of ordinary concrete. The design of the supporting parameters of flexible formwork GER was satisfactory in the No. 31342 working face of the Daichiba Coal Mine. The overall deformation of the roadway is small, and a decent effect is obtained with respect to retaining the roadway. Hence, the technical challenge of enacting GER in medium-thick coal seams with a high dip angle under the filling and supporting modes has been resolved successfully.